Transdisciplinary research before, during and after COVID-19 vaccination in Chile: a virtuoso collaboration with future perspectives - Torres, Juan Pablo; Basso, Leonardo; Saure, Denis; Zuñiga, Marcela; Couve, Andrés; Farfán, Mauricio; de la Maza, Verónica; Campos, Nelson; O’Ryan, Miguel (Frontiers in Public Health, 2024)
The COVID-19 pandemic brought about many challenges requiring urgent attention to lessen its severe health impacts. In March 2020, the Chilean government, including health and science authorities, put in place a strategy to gather essential evidence for making effective public health decisions. A major strength of this strategy was the active involvement of the scientific community, utilizing transdisciplinary approaches to tackle crucial issues and support decision-making by policymakers. Collaborations were fostered among the government, public and private institutions, and academic bodies at every stage of the pandemic. By concentrating on critical questions, this approach laid the groundwork for the collective effort documented in this report, which highlights the collaboration between the Instituto de Sistemas Complejos de Ingeniería (ISCI), the Faculty of Medicine of the University of Chile, government authorities, and industry stakeholders. Early in the pandemic, it was vital to collect evidence on how to minimize the spread and impact of the infection before vaccines were widely available. This involved examining the dynamics of SARS-CoV-2 infection in children, evaluating the effects of quarantines on mobility, implementing strategies for broad PCR testing for SARS-CoV-2, and investigating pool testing for large populations. The urgent task of reducing disease severity and transmission posed a significant challenge, as it was crucial to prevent healthcare systems from being overwhelmed. Studies were carried out to forecast the need for ICU beds at the local level using mathematical models. Furthermore, innovative methods, such as using cellphone mobility data to identify infected individuals and optimize population sampling, were explored after the initial wave of the pandemic. Chile acted swiftly in addressing vaccination through a top-level scientific advisory board, even before vaccines were accessible. Investigations conducted during this period included population-based assessments of vaccine effectiveness, which helped build public trust and supported the case for booster shots and potentially vaccinating children. These studies and partnerships, detailed in this report, have offered valuable insights that will guide future strategies in a post-pandemic era. Significantly, initial estimates suggest that this collaborative effort involving academia, the public sector, and private industry saved around 3000 lives and over 300 million USD.